Behavior of reinforced concrete slabs under low-velocity impact - Xiao, Yao (2018)
Fifteen 1200 x 1200 x 150 mm (47.2 x 47.2 x 5.9 in.) reinforced concrete (RC) slabs were tested under low-velocity impact loadings. These slabs were fixed on their four sides and vertically impacted by a drop-weight system. The influences of impact energy, diameter of impacted area, and nose shape of impactor on the damage of RC specimens are studied. The damage of slabs under low-velocity impact increases with increasing impact energy. Moreover, punching shear failure mode was observed for all the specimens that failed during the test. Besides experimental work, three-dimensional (3-D) finite element (FE) analysis was conducted using the LS-DYNA software to help determine the impact energy that would cause punching shear failure of RC slabs. In the FE model, 3-D elements with strain-rate-sensitive material models were used to model concrete and steel reinforcement. The support and impactor were idealized as rigid body. Based on the results from FE analysis, two dimensionless empirical equations are proposed in term of various parameters to assess the energy capacity of slab under low-velocity impact.